Autism spectrum traits in normal individuals: a preliminary VBM analysis - Focquaert, Farah; Vanneste, Sven (Frontiers in Human Neuroscience, 2015)
In light of the new DSM-5 autism spectrum disorders diagnosis in which the autism spectrum reflects a group of neurodevelopmental disorders existing on a continuum from mild to severe expression of autistic traits, and recent empirical findings showing a continuous distribution of autistic traits in the general population, our voxel based morphometry study compares normal individuals with high autistic traits to normal individuals with low autistic traits. We hypothesize that normal individuals with high autistic traits in terms of empathizing and systemizing (HS/LE) share brain irregularities with individuals that fall within the clinical autism spectrum disorder. We find differences in several social brain network areas between our groups. Specifically, we find increased grey matter volume in the orbitofrontal cortex, the cuneus, the hippocampus and parahippocampus and reduced grey matter volume in the inferior temporal cortex, the insula and the amygdala in our HS/LE individuals. Our findings are in line with brain abnormalities typically reported in autism spectrum disorders and therefore support a dimensional view of autistic traits from a neurobiological perspective.